DESCRIPTION LEVEL KNOWLEDGE STUDENT ABOUT BASIC LIFE SUPPORT IN SENIOR HIGH SCHOOL MUHAMMADIYAH 1 GRESIK - Rizal Nurul Fajar; Cucuk Rahmadi Purwanto; Hafna Ilmy Muhalla (Journal of Vocational Nursing)
Introduction: Basic Life Support (BLS) is a series of help First Which done in situation emergency when somebody has experienced vital organ failure that could threaten their life. To some extent problems, circumstances emergency Which experience stop the heart And stop breathing until arrive on service dire emergency need duration Which more short. Besides the range distance traveled, the patient's prognosis is also influenced by the early management when conditions that require basic life support (BLS) are found. Until now, only a few of those with cardiac arrest and respiratory arrest get basic life support measures (BLS) from residents or people who look at location incidents. The purpose of this research is to know a description of the level of knowledge of students about life support elementary school at SMA Muhammadiya 1 Gresik. Methods: Method quantitative with a descriptive approach with a total of 133 respondents. the sampling technique used in the study This is Simple Random sampling, where the sample is taken from the population at random. This research uses a data collection instrument in the form of a questionnaire containing questions about assistance basic living (BLS). Results: from this study, it is known that the majority of students own knowledge Enough 71 that is (53.1%), And part small students own knowledge not enough that is 15 (11, 8 %). Conclusions: Study This expected can make input For developing knowledge students about help life base through activity extracurricular Cross Red Teenagers and Scouts.